Testing the Rhetoric: Application of Active Learning Strategies in Logic and Critical Thinking Classrooms– Lessons from University of Gondar, Ethiopia - Muluye, Ketemaw Tiruneh (International Journal of Social Sciences and Management, 2020)
The purpose of this research was to examine the implementation of Active Learning Strategies (ALSs) in logic and critical thinking classrooms by focusing on freshman students of Gondar University. For this purpose, a concurrent triangulation mixed approach and case study design were employed. The data were collected through questionnaires (n=361), interviews and document analysis. Accordingly, the utilization of ALSs in logic and critical thinking classrooms is found to be negligible. Though buzz group discussions and presentations were found to be preferable as compared to other ALSs, they are utilized in a rare manner. Factors related with the directives of the Ministry, motivation of the instructors and students were found to have an influence on the utilization of ALSs. This implies though the Ministry claims that it is committed for the utilization of ALSs, its directives are not found to be complimentary with its rhetoric for the utilization of ALSs. Int. J. Soc. Sc. Manage. Vol. 7, Issue-2: 78-85